Growth Parameters of Sentani Gudgeon Fish (Oxyeleotris heterodon) in Sentani Lake, Papua - Herlan Herlan; Tuah Nanda Merlia Wulandari (Universitas Muhammadiyah Palembang, 2021)
ABSTRACTThe Sentani Gudgeon Fish (Oxyeleotris heterodon, Weber 1907) from the family Butidae with the general name Sentani Gudgeon is known locally as Gabus Malas and Himen. Sentani Snakehead Fish is one source of animal protein that is very important for the community around Lake Sentani. The population of the Sentani Gudgeon Fish species is at a crucial level. The issue could be affected by environmental pressures, continuous catches, competition with introduced species from outside Papua, intensive predation systems, and imbalances in ecological systems. The condition made a decline in population size until it became extinct. Gudgeon Sentani fish is the main target of catching in the lake. This condition significantly affects stock, size when first captured, population decline, reproductive cycle, and average catch. Until now, data and information on the growth of snakehead fish as the basis for fisheries management in the waters of Lake Sentani are not widely known. Considering the importance of preserving the native species of Lake Sentani, especially the Snakehead Fish, efforts to manage the fisheries in Lake Sentani's waters are urgent. This research was conducted in March - October 2020, located at Lake Sentani. The specimens were obtained from the catch of fishers with various gill nets and chopsticks. Enumerators or field assistants assisted the recording of the number and measurement of the total length of fish caught by fishermen daily. The results of the analysis showed: asymptotic size (L?) 46.20 cm, growth coefficient (K) 0.29, the total mortality rate (Z) 0.80 per year, natural mortality (M) 0.74 per year, the mortality rate due to fishing (F) 0.06 per year and exploitation rate (E) 0.075 per year.